Do charges delocalize over multiple molecules in fullerene derivatives?. Issue 17 (9th December 2015) - D'Avino, G.; Olivier, Y.; Muccioli, L.; Beljonne, D.
Abstract : We address the question of charge delocalization in amorphous and crystalline fullerene solids by performing state of the art calculations encompassing force-field molecular dynamics, microelectrostatic and quantum-chemical methods. Abstract : We address the question of charge delocalization in amorphous and crystalline fullerene solids by performing state of the art calculations encompassing force-field molecular dynamics, microelectrostatic and quantum-chemical methods. The solution of a tight-binding model built from spatially (down to atomistic scale) and time (down to fs) resolved calculations yields the density of electronic states for the charge carriers and their energy-dependent intermolecular delocalization. Both pristine C60 and the soluble PC61 BM/PC71 BM acceptors may sustain high-energy states that spread over a few tens of molecules irrespective of morphology, yet electrostatic disorder (mostly dipolar and static in nature) makes the thermally available electron states collapse to hardly more than one molecule in PC61 BM/PC71 BM, while it has a much more limited impact in the case of the bare C60 . Implications of these results for charge transport and exciton dissociation at donor–fullerene interfaces are discussed.